Multi-Index Monitoring and Evaluation on Rock Burst in Yangcheng Mine - Yunliang Tan; Yanchun Yin; Shitan Gu; Zhiwei Tian (Shock and Vibration)
Based on the foreboding information monitoring of the energy released in the developing process of rock burst, prediction system for rock burst can be established. By using microseismic method, electromagnetic radiation method, and drilling bits method, rock burst in Yangcheng Mine was monitored, and a system of multi-index monitoring and evaluation on rock burst was established. Microseismic monitoring and electromagnetic radiation monitoring were early warning method, and drilling bits monitoring was burst region identification method. There were three identifying indexes: silence period in microseismic monitoring, rising period of the intensity, and rising period of pulse count in electromagnetic radiation monitoring. If there is identified burst risk in the workface, drilling bits method was used to ascertain the burst region, and then pressure releasing methods were carried out to eliminate the disaster.